Synthetic receptors prepared by organized assembly of organic molecules. - Takeuchi, T. (IEEE Engineering in medicine and biology magazine)
Synthetic organic molecular approaches to prepare materials for fabricating molecular functional devices is one of the most attractive themes for chemists to pursue. Organized assemblies of organic molecules could be expected to exhibit new functionality in the resulting structure. However, the desirable functionality sometimes requires structure that is too complicated to synthesize by means of conventional synthetic techniques. In 1988, Lehn elucidated the concept of supramolecular chemistry in his Nobel lecture, which involved the construction of complicated molecules by self-assembling of small molecules with multiple weak-bond formation, allowing new functions to be induced. Considerable efforts have been made to develop supramolecular self-assembling systems. It appears that such systems have a great potential for the preparation of functional molecules in the field of molecular electronics and biosensor technology. In this article, we describe two topics with regard to self-assembly-induced molecular recognition systems including (1) metal ions-mediated supramolecular assembling of small molecules to form well-defined structures in aqueous solution and (2) molecular imprinting, the combined technique of self-assembling and cross-linked synthetic polymer synthesis to prepare synthetic receptors/enzymes. We present several examples and demonstrate the possibility of new frontier technologies of molecular architecture in designed chemistry, producing a new class of functional molecules.